Development of Poetry Appreciation Teaching Materials Through Interpretation, Demonstration, and Evaluation (IDE) Techniques for Students of Indonesian Language and Literature Education Study Program, Faculty of Language and Arts, Universitas Negeri Jakarta - Ayu Puspa Nanda; Etsa Purbarani; Sifa Awalunisa Al Mugni; Raysa Anggraini Puspita; Rahma Alia; Ratu Dzakiya Aryani Putri (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
This study was motivated by the limited effectiveness of poetry appreciation teaching materials, which remain largely theoretical and fail to actively engage students in interpreting and expressing the aesthetic meaning of poetry. The purpose of this research is to develop poetry appreciation teaching materials based on the Interpretation, Demonstration, and Evaluation (IDE) technique that are applicable, interactive, and contextual for students of the Indonesian Language and Literature Education Study Program, Faculty of Language and Arts, Universitas Negeri Jakarta. The research employed a Research and Development (RnD) method using the ADDIE model, which includes needs analysis through questionnaires and interviews, design, and draft preparation of the teaching materials. The results show that 90% of respondents support the implementation of the IDE technique, as it enhances students’ understanding, aesthetic sensitivity, and expressive skills in poetry appreciation.